THE INFLUENCE OF THE SCHOOL OF MOVEMENT, PARENTS' OCCUPATION, AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTERESTS OF STUDENTS IN SENIOR HIGH SCHOOL - Sudarwati, Ninik; Chalimah, Chalimah; Nurhayati, Dies (PT. Jurnal Center Indonesia Publisher, 2025)
To establish a good business, a strong entrepreneurial spirit is needed. SMAN 1, SMAN 2, SMAN 3 Jombang students can be supported by the education of the driving school project, parents' work, and family environment, which can shape the mindset and interest of each student in the world of entrepreneurship. Based on this phenomenon, the authors are interested in conducting research by taking the title: